Perirhinal firing patterns are sustained across large spatial segments of the task environment - Jeroen J. Bos (Nature Portfolio, 2017)
Spatial navigation and memory depend on neural coding of an organism’s location as well as large-scale knowledge of the environment, but how animals organize information in task-relevant spatial segments is not well understood. Here the authors show that, in rats, perirhinal neurons perform integrative operations, globally specifying where, in the task context, an animal is located.